2014
DOI: 10.1891/2168-6653.28.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Transition Personnel Preparation in Rehabilitation Counselor Education Programs

Abstract: Rehabilitation counselors are increasingly called on to provide services to transitionaged youth. However, preparation and training efforts are not sufficient to ensure that counselors have the required knowledge and skills to adequately serve these students and young adults. The purpose of this study was to investigate how secondary transition-content is infused in rehabilitation counseling programs. Specifically, (a) which transition-related competencies are considered to be most important; (b) how much inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Looking ahead, in 2017, the priority focus area is on preparing personnel to serve children with high-intensity needs across an array of disabilities (e.g., multiple disabilities, significant cognitive disabilities; USDOE, 2017). This lack of focus on transition-focused personnel preparation funding further narrows the scope of graduates with the knowledge and skills required to support the transition needs of youth with disabilities (Miller, Lombard, & Hazelkorn, 2000; Plotner & Fleming, 2014). In contrast to the funding pattern, many participants indicated that disability-specific training should be secondary to a foundation in transition-related knowledge and skills, as graduates will likely work with a wide spectrum of students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking ahead, in 2017, the priority focus area is on preparing personnel to serve children with high-intensity needs across an array of disabilities (e.g., multiple disabilities, significant cognitive disabilities; USDOE, 2017). This lack of focus on transition-focused personnel preparation funding further narrows the scope of graduates with the knowledge and skills required to support the transition needs of youth with disabilities (Miller, Lombard, & Hazelkorn, 2000; Plotner & Fleming, 2014). In contrast to the funding pattern, many participants indicated that disability-specific training should be secondary to a foundation in transition-related knowledge and skills, as graduates will likely work with a wide spectrum of students.…”
Section: Discussionmentioning
confidence: 99%
“…Considering transition professionals’ duties require competency in various areas (e.g., understanding of adult service system, interagency collaboration), it was perhaps no surprise that participants emphasized the positive aspects of interdisciplinary collaboration in program development. Transition personnel preparation programs that are composed of faculty from different disciplines (e.g., rehabilitation, counseling) could serve as a positive model in program development (Plotner & Fleming, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With the influx of transition-focused professionals and the need for improved transition planning and services, university personnel preparation programsfocusing on transition have emerged. The current literature on transition preservice professional development reports limited transition content infused into special education (Anderson et al, 2003; Morningstar & Benitez, 2013) and rehabilitation counseling training programs (Plotner & Fleming, 2014). Morningstar and Benitez (2013) reported that teachers only complete an average of one course in transition with almost having no transition courses.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…Morningstar and Benitez (2013) reported that teachers only complete an average of one course in transition with almost having no transition courses. Furthermore, Plotner and Fleming (2014) surveyed rehabilitation counselor preparation program faculty and found that the majority of faculty do not believe that their rehabilitation counseling program offers enough content related to secondary transition. Overall, more than half of the respondents strongly disagree or disagree that their professional development opportunities have fully prepared them.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…Keterlibatan GBKS dalam memberikan perkhidmatan bimbingan dan kaunseling di Malaysia terhadap MBK seperti garis panduan yang dibekalkan menjadi persoalan apabila hasil kajian lepas mendapati bahawa kaunselor kurang melaksanakan perkhidmatan kepada klien pelbagai budaya (Adams, 2015;Hanani Harun Rasit, 2014;Rafidah Aga Mohd Jaladin, 2013), kurang bersedia dalam berhadapan dan memberi perkhidmatan kaunseling kepada MBK (Arnold, 2010;Lee, 2015;Nichter & Edmonson, 2005;Plotner & Fleming, 2014;Rafidah Aga Mohd Jaladin, 2013), kurang kompeten (Aksoy & Diken, 2009), dan kurang mempunyai pengetahuan dalam pendidikan khas atau ketidakupayaan (Hanani Harun Rasit, 2014;Lee, 2015;Tait, 2013;Zahra, 2014). Manakala, kajian yang dilaksanakan oleh Lee (2015) turut mendapati kaunselor tidak mempunyai pengetahuan mengenai pendidikan khas dan polisi serta mempunyai beban kes yang banyak.…”
Section: Wwwmsocialworkcomunclassified